Use of fluorescence-based sensors to determine the nitrogen status of paddy rice. (10th January 2013) - LI, J. W.; ZHANG, J. X.; ZHAO, Z.; LEI, X. D.; XU, X. L.; LU, X. X.; WENG, D. L.; GAO, Y.; CAO, L. K.
SUMMARY: The environmental concern about diffuse pollution from nitrogen (N) fertilizers has led to increased research on the diagnosis of crop N status. The SPAD chlorophyll (Chl) meter is the most commonly used tool for rice ( Oryza sativa L.) N status diagnosis, but measurements are conducted at a specific point and readings are affected by different leaf positions. Many measurements per plant must be taken in order to increase the accuracy of N status diagnosis, which limits its application. The present paper attempts to determine rice N status at the canopy level using Multiplex ®, a new hand-held optical fluorescence sensor. The fluorescence emission of rice leaves under light excitation was utilized by Multiplex ® to non-destructively assess rice leaf Chl and phenolic compound content. A field experiment was conducted in 2011 using a completely randomized split-plot design, with main-plot treatments being six N fertilizer application rates and subplot treatments being different plant densities. Leaf Chl and phenolic compounds were evaluated using the ratio of far-red fluorescence (FRF) to red fluorescence (RF) emission under red light excitation (simple fluorescence ratio, SFR_R) ( R 2  = 0·35, P  < 0·01) and the ratio of decadic logarithm of red to ultra-violet (UV) fluorescence emission ( R 2  = 0·30, P  < 0·01), respectively. Both SPAD reading and fluorescence-based indices including flavonoids (FLAV), nitrogen balance index (NBI_R) and SFR_R could be used to predict rice leaf N contents. The canopy FLAV, SFR_R and NBI_R were all highly correlated to average SPAD readings ( R 2  > 0·70 in most cases, P  < 0·01). Therefore, Multiplex ® can be used as an alternative to SPAD to determine rice N status in paddy fields.